Laboratory Analysis of the Anti-Infectious Activity of Quantum Dots and Bioconjugates Based on Them in the Aspect of the Prospects for the Treatment of Inflammatory Diseases of the Eye. Experimental Research (Part 3) - V. O. Ponomarev; V. N. Kazaykin; A. V. Lizunov; A. S. Vokhmintsev; I. A. Weinstein; S. M. Rozanova; M. V. Kirf (Oftalʹmologiâ)
This article presents the third part of an experimental study on the prospects and possibilities of using quantum dots and bioconjugates created on their basis in the treatment of inflammatory diseases of the eye. Taking into account the previously obtained results on the possibility of “safe” use of CdTe/Cd and InP/ZnSe/ZnS quantum dots on an animal model under conditions of intravitreal administration, the aim of the current stage was to analyze their antimicrobial activity in a bacteriological laboratory.Materials and methods. As QDs, we took two types of artificial fluorophores capable of generating superoxide radicals synthesized according to a special technical assignment at the Federal State Unitary Enterprise “Research Institute of Applied Acoustics”, Dubna, Moscow Region: type 1 — colloidal solution of QD CdTe / Cd MPA 710 10 % of the mass. Type 2 — colloidal solution of QD InP / ZnSe / ZnS 650 10 % wt. The study included “museum” and nosocomial strains of microorganisms, and the activity of points was assessed using the diskdiffusion method, followed by an assessment of the zones of inhibition of bacterial growth. Concentrations of 0.1 %, 0.01 %, and 0.001 % quantum dots were tested, as well as solutions of bioconjugates (antibiotic + quantum dots) of Vancomycin, Levofloxacin, Ceftazidime and Cefotaxime.Results. Based on the data obtained, it was concluded that quantum dots potentiate the action of the sensitivity of individual microorganisms, both outpatient and hospital strains.